BEYOND THE COGNITIVE: EMPIRICAL EVIDENCE OF THE CRUCIAL ROLE OF SOCIOEMOTIONAL SKILLS IN LEARNING IN COLOMBIAN ELEMENTARY SCHOOL - Diana Mayerli Antolinez Buitrago; Betty Milena Porras Gómez; Diana Sunce Puentes (LÍNEA IMAGINARIA, 2025)
The purpose of this article, by the nature of a scientific essay, is to reflect on how current education faces circumstances that have left important marks on society, such as the technological advances and transformations that have gone hand in hand with different processes, such as teaching and learning; in this sense, it is observed that different contents of the curricular design use technologies as instructional resources that have tried to bring the topics to the students, and that is why the present general objective emerges, which is framed in: to reflect on socio-emotional skills in learning in Colombian primary basic education (HSEAEBPC); the methodology fits into a documentary analysis, which resulted in a scientific essay that becomes a significant contribution so that teachers can have at their disposal concepts and teaching tools that aim to strengthen socio-emotional skills in students at the primary level; However, it is of utmost importance to recognize that one of the most impactful aspects of the educational process goes beyond the cognitive and crucial role of teachers in making the teaching process a theoretical and practical journey that is quite accessible for those responsible for defining quality education, tailored to the demands of the general population, considering the purpose of the educational system.